Further delineation of Borrelia burgdorferi Restriction-Modification system and understanding antibiotic resistance in Borrelia afzelii - Demchyshyn, Stepan Stepanovych (Jihočeská univerzita, 2016)
The aim of this thesis was to further the understanding of restriction-modification and the homology within the restriction-modification genes in various Borrelia species including Borrelia afzelii as well as to investigate spontaneous antibiotic resistance within this particular Borrelia species.
Further delineation of Borrelia burgdorferi Restriction-Modification system and understanding antibiotic resistance in Borrelia afzelii
Keywords: Borrelia; Lyme disease; restriction modification; enzymes; ticks; Borrelia; Lyme disease; restriction modification; enzymes; ticks